2020
DOI: 10.1002/ejoc.202001003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Straightforward, Photoinduced Alkylations of Electron‐Rich Heterocompounds with Electron‐Deficient Alkyl Bromides in the Sole Presence of 2,6‐Lutidine

Abstract: Alkylations of simple electron-rich heterocompounds deliver valuable target structures in bioorganic and medicinal chemistry. Herein, we present a straightforward and photosensitizer free approach for the photoinduced CC coupling of electron-rich unsaturated heterocompounds with alkyl bromides using 405 nm and 365 nm irradiation. Comprehensive mechanistic studies indicate the involvement of 2,6-lutidine in the formation of a non-covalently bound intermediate to which the function of a photosensitizer is attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…During the mechanistic investigation of a light-induced α-alkylation according to MacMillan, it was observed that although the photosensitizer could be omitted, the base 2,6-lutidine is indispensable for a successful reaction. ,, …”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…During the mechanistic investigation of a light-induced α-alkylation according to MacMillan, it was observed that although the photosensitizer could be omitted, the base 2,6-lutidine is indispensable for a successful reaction. ,, …”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…[73] In 2020, Trapp and co-workers explored a straightforward and photoinduced alkylation of heterocompounds with alkyl bromides under light irradiation (Scheme 17). [76] Some substituted furan, thiophene, pyrrole and indole derivatives were obtained through this photocatalyzed approach. The formation of colored EDA complex 92 from colorless 2,6-lutidine and colorless electron-deficient alkyl bromide was confirmed by UV/Vis spectra.…”
Section: Alkylation Of Aromatic Compoundsmentioning
confidence: 99%
“…Following the reaction progress by 1 H NMR shows the formation of intermediate I2 (Figure SI3), which upon the addition of water converts to a corresponding carboxylic acid 5 or into product 4 upon addition of 2,6-lutidine as the base. On the basis of these experiments and related literature precedents, a possible reaction mechanism is shown in Scheme c. The pyrazolo­[1,2- a ]­pyrazole 1 was first excited with visible light to form the excited 1* , which underwent single electron transfer (SET) with diethyl bromomalonate to generate the corresponding radical cation of 1 .…”
mentioning
confidence: 93%
“…When the N -methylpyrrole substituted bicycle 1 was reacted under standard conditions, the corresponding N -acryloyl substituted pyrazole 4o was isolated in a 15% yield, together with the C5′ malonyl substituted derivative 4o′ in a 50% yield. The coupling of this electron-deficient malonate radical at the C2 position with electron-rich arenes, such as pyrroles, thiophenes, and furans under visible light-mediated conditions was documented by Stephenson, Trapp, Noël, and Wu . To demonstrate the scalability of the method, a gram-scale experiment was performed to give 4a with a comparable 80% product yield…”
mentioning
confidence: 99%